Cultural Barbarism in Relation to Women?: Huntington's Theory and the German Case of Mass Sexual Assaults on New Year's Eve 2015 - Pasamonik, Barbara (The review of faith & international affairs, 2019)
This article analyzes, from the perspective of Samuel Huntington's hypothesis about a "clash of civilizations," the nature of the mass sexual assaults on women committed by migrants coming from non-European countries on New Year's Eve 2015 in Germany. It is argued that the fundamental cultural factor triggering this criminal behavior was the clash of a patriarchal culture of honor and Islamic ethical code with liberal Western urban culture. But the cultural factor was not isolated. The "non-cultural" factors, i.e. social, biological, psychological, demographic, and economic factors, played important role.